Tom Clancy terminal velocity [large type] - Woodward, M. P. (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel, 2025)
"A string of savage murders in the United States seems unrelated until the FBI makes a shocking discovery: a decade ago, all of the murder victims were involved in a raid to eliminate the Umayyad Revolutionary Council, a vicious terror group that--were it not for John Clark and the Campus--would have perpetrated the most devastating attack against critical American infrastructure in history. Now it appears they're back, with a next-generation leader hell-bent on revenge. Mary Pat Foley, Director of National Intelligence, greenlights an op for the Campus to cut the head off the snake. Clark taps ex-Delta commando Bartosz "Midas" Jankowski to lead a kill team deep into the mountains to snuff out the charismatic terror leader. But when the hunters become the hunted, it's up to Jack Rayan Jr. to avert disaster amid a deadly power game of nations vying for control of the disputed region. On a rapid covert ingress from neighboring India, he'll traverse the Himalayan wilderness with a rifle on his back and a tough Mujahadin fighter by his side. Jack knows time is growing short--he must save his team and lead them into position to be the first to hit terminal velocity"--